Gaseous Elemental Mercury Emissons from Selected E-Waste Processing Facilities in Turkey - Kurt-Karakus, Perihan Binnur; Odabasi, Mustafa; Akcetin, Merve Ozkaleli; Birgul, Askin; Kara, Melik; Dumanoglu, Yetkin; Wania, Frank (Mehmet Sinan Bilgili, 2022)
The amount of mercury contained in each unit of electrical and electronic waste (WEEE) is low (about 2-10 mg per equipment). However, it is estimated that all the mercury in the annually produced WEEE accounts for about 22% of the world mercury consumption. Facilities focusing on WEEE recycling have grown enormously in recent years and unfortunately some of this e-waste contains mercury or mercury compounds. The mercury may be released into the environment from consumer products during the recycling processes. Additionally, the recyclers themselves face the possibility of mercury exposure. Environmentally sound management of WEEE needs to involve the informal recycling industry which plays an important part in waste management. The global Minamata Convention on Mercury (Hg), created recently through the United Nations Environmental Programme, requires its signatories to perform improved atmospheric Hg monitoring and characterization of Hg sources. In this study, we evaluate the gaseous mercury emissions from selected licensed WEEE facilities to the atmosphere in different provinces of Turkey by employing a passive air sampling technique.
6th EurAsia Waste Management Symposium (EWMS) -- OCT 24-26, 2022 -- Istanbul, TURKEY
Keywords: waste electric and electronic equipment (WEEE); e-waste processing; mercury; air; passive sampling